Polyphenols as Antitumor Agents Targeting Key Players in Cancer-Driving Signaling Pathways - Cháirez-Ramírez, Manuel Humberto; de la Cruz-López, Karen Griselda; García-Carrancá, Alejandro (Frontiers in Pharmacology, 2021)
Polyphenols constitute an important group of natural products that are traditionally associated with a wide range of bioactivities. Polyphenols, already available in nutraceuticals or as dietary supplements including apigenin, quercetin, curcumin, resveratrol, Epigallocatechin 3-gallate (EGCG), and kaempferol, have been shown to regulate signaling pathways that are central for cancer development, progression, and metastasis. Here we describe novel mechanistic insights on the effect of this group of polyphenols on key elements from signaling pathways. We describe the modifications and regulations induced by these polyphenols on elements from several signaling pathways, including PI3K, Akt, mTOR, RAS, and MAPK, and particularly those affecting the tumor suppressor p53 protein. Modifications in p53 induced by these polyphenols include the regulation of gene and protein levels, and posttranslational modifications such as phosphorylation, acetylation, and ubiquitination, which influence the following: stability; subcellular location; activation of new transcriptional targets and the role of p53 in response to DNA damage; apoptosis control; cell-cycle regulation; senescence, and cell fate. Thus, a profound understanding of the effects that polyphenols have on these key players in cancer-driving signaling pathways will certainly lead to better-designed targeted therapies, with less toxicity for cancer treatment. The scope of this review centers on the regulation of key elements of cancer signaling pathways by the most studied polyphenols and highlights the importance of a deep understanding of these regulations for improving cancer treatment and control with natural products.